2014
DOI: 10.1260/1369-4332.17.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Performance Testing and Cyclic Behavior of Buckling-Restrained Braces with H Cross Section Unrestrained Segments

Abstract: The hysteretic behavior of four buckling-restrained braces (BRBs) with H cross section unrestrained segment was tested under cyclic load. The transformation of the unrestrained segment's section from crisscross shape to H shape can improve the moment-resistance capacity of unrestrained segment significantly and avoid buckling instability of unrestrained segment effectively due to evident stiffness enhancement. BRBs were designed according to Chinese codes, the load-carrying elements of BRBs were fabricated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The cross-sectional shape of the inner steel core can vary (e.g. Jia et al [9]), but typically the yielding segment of the core is a plate with rectangular section. To minimize friction between the core and restraining member, several kinds of debonding material [10,11] or air gap have been used [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The cross-sectional shape of the inner steel core can vary (e.g. Jia et al [9]), but typically the yielding segment of the core is a plate with rectangular section. To minimize friction between the core and restraining member, several kinds of debonding material [10,11] or air gap have been used [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was suggested that when steel moment-resistant frames (SMRFs) were subjected to design-based earthquakes (DBE) ground motions (10% in 50 years), the residual drifts of SMRFs were varied from 0.5% to 1.2% (Adeli et al, 2012). Many research results show that the low-cycle fatigue failure of steel in structures will eventually be caused by cumulative damage (Afsar et al, 2018; Jia et al, 2014; Krawinkler and Zohrei, 1983; Li et al, 2019). In view of this, the low-cycle fatigue life of BRBs needs to be extensively and quantitatively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a comprehensive experimental program (Merritt et al, 2003;Xie, 2005;Jia et al, 2014) BRBs deliver ductile, stable, and repeatable hysteretic behavior, and the plastic deformation capacity of the braces exceeds the specified requirements in terms of both ultimate deformation and cumulative plastic strain. Ju et al (2009) conducted component tests on the effect of the thickness of the constraining tube and the length of the unconstrained length of the H-shaped core ends on the maximum strength and the energy dissipation capability of BRB.…”
Section: Introductionmentioning
confidence: 99%